Inspiratory muscle training in stroke patients with congestive heart failure: A CONSORT-compliant prospective randomized single-blind controlled trial. Issue 37 (September 2016) - Chen, Po-Cheng; Liaw, Mei-Yun; Wang, Lin-Yi; Tsai, Yu-Chin; Hsin, Yi-Jung; Chen, Yung-Che; Chen, Shyh-Ming; Lin, Meng-Chih
Abstract: Background: Cardiopulmonary function can be adversely affected after a cerebrovascular accident in patients with congestive heart failure (CHF). The aim of this study was to investigate the efficacy and feasibility of inspiratory muscle training (IMT) for stroke patients with CHF. Methods: A prospective randomized single-blind controlled trial was conducted in a single tertiary medical center in southern Taiwan between May 2011 and July 2015. Forty-one patients were enrolled, of whom 21 completed the study (IMT group n = 11 and control group n = 10). Both groups participated in a conventional stroke rehabilitation program. Patients in the IMT group received an additional IMT program beginning with an intensity of 30% maximal inspiratory pressure (MIP), then increased by 2cmH2 O each week for 30 minutes daily for at least 5 days a week for 10 weeks. MIP, maximal expiratory pressure, spirometry, resting oxyhemoglobin saturation, modified Borg Scale, Fatigue Assessment Scale, and Barthel Index were assessed in each patient. Results: There were significant differences from baseline in MIP ( P = 0.008), percent predicted forced vital capacity ( P = 0.033), forced expiratory volume in 1 second (FEV1) ( P = 0.008), percent predicted FEV1 ( P = 0.008), and Barthel Index ( P = 0.012) in the IMT group, and Barthel Index ( P = 0.027) in the control group. There were significant differences between groups in MIP (20.91 ± 19.73 vs −9.00 ± 26.01, adjusted P value = 0.023) and Barthel Index (24.55 ± 22.30 vs 7.50 ± 8.25, adjusted P value = 0.044). Conclusion: The 10-week IMT was feasible and effective in improving inspiratory force and activities of daily living for the stroke patients with CHF.